Problems of diagnosing focal cortical dysplasia - K. D. Yakovleva; E. A. Kantemirova; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния, 2021)
Focal cortical dysplasia (FCD) is one of the most common causes in developing pharmacoresistant epilepsy. We present the clinical case of the patient with generalized seizures. Routine electroencephalography (EEG) data registered diffuse epileptiform activity that allowed to diagnose genetic  eneralized epilepsy and pharmacoresistant course of seizures.After performing magnetic resonance imaging using the epileptological program and video-EEG-monitoring, the diagnosis was revised: structural focal epilepsy with seizures with  focal onset with oroalimentary, gesture automatisms in the right hand, bilateral tonic-clonic, uncompensated by levetiracetam monotherapy (1500 mg/day). Background disease: congenital  malformation of the brain: FCD in the basal parts of the left temporal lobe. Lacosamide was added to the therapy in the drug dose 300 mg/day, and the frequency of epileptic seizures decreased. Differential diagnosis between genetic generalized  epilepsy and structural epilepsy with FCD usually poses no  obstacles. However, in some cases, structural epilepsy occurs  under the “mask” of generalized epilepsy. Hence, this clinical  case demonstrates the importance of diagnostic measures in the  differential diagnostics of various forms of epilepsy to determine  further tactics of patient management.